Diagnostic Dilemma in cases of Ectopic Pregnancy: a five year prospective study at Tribhuvan University Teaching Hospital - Gurung, G.; Rana, A. (Journal of Institute of Medicine Nepal, 2007)
Objective: To determine the incidence of ectopic pregnancy in TUTH and to find out the atypical presentations of ectopic pregnancy that had lead difficulties in diagnosing the cases of ectopic pregnancy leading to increase morbidity. Study design: It is a prospective, descriptive study done in Dept. of Obs/Gyn, TUTH, during the period of Baisakh 2057 – Chaitra 2061 (April 2001- April 2005). Results: There were total of 174 cases of ectopic pregnancy during the period of five years accounting 1.15 % of all deliveries. Majority of them were multipara (P2-3)39.5%. Among the 174 women 48.9% carried the risk factors. The commonest risk factor being secondary subfertility (25.9%) followed by h/o D&C (18.5%) and reversal of tuballigation (17.6%). Not all the patients had the classic triad of ectopic pregnancy (98.9% had pain, 70.7% had amenorrhea and only 58% had bleeding). Only 20% presented with syncope (the typical symptom of ruptured ectopic pregnancy). The condition was confirmed by USG in 82%. Urinary hCG was present in 97.1%. Mild anaemia (8-10gm% Hb) was present in 46.6% cases where as only 4% had severe anaemia <6gm. Among these anaemic patients 60% needed blood transfusion. Twenty five (14.3%) out of 174 cases had presented with atypical symptoms resulting difficulty in diagnosis (8 cases confused with GI disorders and 17 cases with gynecological disorders). Conclusion: USG and urinary hCG are not confirmatory diagnostic tools in all cases of ectopic pregnancies. For that serum hCG and diagnostic laparoscopy should be included to improve in the management of ectopic pregnancy. Journal of Institute of Medicine Vol.28(1) 2006